2009
DOI: 10.1258/la.2008.007004
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic analysis of apolipoproteins in postprandial hypertriglyceridaemia rabbits

Abstract: The postprandial hypertriglyceridaemia (PHT) rabbit, developed as a new animal model of metabolic syndrome, is characterized by PHT, central obesity and glucose intolerance. For detailed investigation of lipid metabolism characteristics in PHT rabbit, the plasma levels of apolipoproteins A-I, B, C-II, C-III and E were measured. Movements of apolipoproteins B100 and B48 were investigated using sodium dodecyl sulphate-polyacrylamide gel electrophoresis to determine whether postprandially increased triglyceride i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Previously it was reported that the retention of chylomicron remnants was caused by the delayed catabolism of exogenous lipids in the blood of PHT. In addition, the lipolytic enzyme lipoprotein lipase and hepatic triglyceride lipase were deficient and that the hepatic uptake of exogenous lipoproteins was delayed in the PHT rabbit [17]. In contrast, cholesterol levels in PHT rabbits were little changed even after feeding.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously it was reported that the retention of chylomicron remnants was caused by the delayed catabolism of exogenous lipids in the blood of PHT. In addition, the lipolytic enzyme lipoprotein lipase and hepatic triglyceride lipase were deficient and that the hepatic uptake of exogenous lipoproteins was delayed in the PHT rabbit [17]. In contrast, cholesterol levels in PHT rabbits were little changed even after feeding.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, a previous report examined the kinetics of various apolipoproteins in PHT rabbit to elucidate the lipid metabolism in PHT. It was shown that apoprotein E, which is necessary for the uptake of chylomicron remnants by the liver, was increased postprandially in PHT [17]. In the SDS-PAGE experiments, apolipoprotein B100 was detected in the PHT rabbits before feeding, and apolipoproteins B100 and B48 were both detected 15 h after feeding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LDLR mRNA in the liver was higher in PHT than in JW rabbits in the postprandial state, hence, the LDL uptake by the liver was not defected. Despite lower cholesterol contents in VLDL compared to LDL, the PHT rabbits contained extraordinarily high levels of VLDL, (9) suggesting that the VLDL-derived cholesterol would partly contribute to the high T-CHO values. Thus, the increase in the T-CHO can be explained by defected apolipoprotein clearance without increase in the CHO biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…(8) Elevated secretion of VLDL from liver and temporary delaying of triglyceride degradation appears to be a direct cause of the postprandial hypertriglyceridemia. (9) …”
Section: Introductionmentioning
confidence: 99%